DETECTING OF PROBABILITY OF FINANCIAL STATEMENT FRAUD USING FRAUD HEXAGON MODEL: Evidence from Indonesian Public Companies - Sahda Purnama Sari; Mamduh Mahmadah Hanafi (Tax Accounting Applied Journal, 2023)
Many of Indonesian public companies had proven guilty that have committed financial statement fraud.The purpose of this research is for detecting financial statement fraud using fraud hexagon model consists of pressure, opportunity, rationalization, ccompetence, arrogance & collusion variabels. The sample in this reaserch specifically chose companies that were proven to have committed financial statement fraud and used logistical regression estimation technique assisted by STATA 14.The results of this reaserch shows that pressure proxied by financial stability, rationalization proxied by total accruals and collusion proxied by state owned enterprises (SOEs) have positive effect significantly on probability of financal statement fraud. Consequently, change of receivables, change of directors, CEO education, CEO narcissism, managerial ownership and CEO duality have negative effect on probability of financial statement fraud. meanwhile, external pressure, financial target, ineffective monitoring and auditor switching have no efffect on probability of financial statement fraud. The fraud hexagon model  can be used for financial statement fraud detection because the results support the collusion variable proxied by state owned enterprises (SOEs) which indicates that regulation, supervision and punishment are still weak for parties proven to have committed financial statement fraud.